Bidirectional partial power converter interface for energy storage systems to provide peak shaving in grid-tied PV plants - Muller, Nicolas; Kouro, Samir; Zanchetta, Pericle; Wheeler, Patrick (2018)
The ever growing participation of modern renewable resources in electric markets has shaken the paradigm of generation-demand constant match. Most modern renewables add intermittent behaviour and high variability to electric markets, forcing other renewables and themselves to perform power curtailment and/or having extra generating units connected to the network to compensate power, voltage and frequency variations. In order to handle this scenario, Energy Storage Systems (ESSs) have risen as enabling technologies capable to provide backup energy to compensate power, voltage and frequency fluctuations and, at the same time, offer additional benefits as ancillary services, peak shaving, load shifting, base load generation, etc. This paper presents a novel bidirectional Partial Power Converter (PPC), as an interface between a Battery ESS (BESS) and a grid-tied Photovoltaic (PV) plant. To obtain a better understanding of the converter, its mathematical model is presented and its operation modes are explained. The main purpose of this configuration is to provide peak shaving capability to a grid-tied PV plant, while providing a high efficiency BESS. Simulation results show the operation of the full system (grid-tied PV plant and BESS), performing peak shaving under a step-down and up in solar irradiation.